The North Karelia Project : 20 year results and experiences - Puska, Pekka; Kansanterveyslaitos; Maailman terveysjärjestö. Euroopan aluetoimisto; Pohjois-Karjala-projekti; Pohjois-Karjala-projektin tutkimussäätiö (National Public Health Institute, 1995)
Summary.
Keywords: Cardiovascular Diseases; Coronary Disease : mortality; Coronary Disease : prevention & control; Feeding Behavior; Health Behavior; Hypertension; Myocardial Infarction; Risk Factors; ennaltaehkäisy; kansanterveys; kuolleisuus; Pohjois-Karjala-projekti; projektit; ravitsemuskasvatus; sydän- ja verisuonitaudit; terveyskasvatus; terveyskäyttäytyminen; förebyggande; folkhälsa; mortalitet; Norra Karelen-projektet; projekt; kostupplysning; hjärt-kärlsjukdomar; hälsofostran; hälsobeteende; Pohjois-Karjala; Norra Karelen